2006
DOI: 10.3171/jns.2006.105.4.621
|View full text |Cite
|
Sign up to set email alerts
|

Long-term response of pituitary carcinoma to temozolomide

Abstract: Pituitary carcinoma is a rare tumor characterized by poor responsiveness to therapy, leading to early death. Reported responses to standard chemotherapy have only been anecdotal, with no single agent or combination demonstrating consistent efficacy in the treatment of patients with this disease. The authors report rare examples of a persistent response to cytotoxic chemotherapy in two patients with pituitary carcinoma. One patient was a 38-year-old man with visual field loss caused by a luteinizing hormone-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(126 citation statements)
references
References 16 publications
3
123
0
Order By: Relevance
“…19 Of the reported cases, 4 of 11 pituitary adenomas 11,14-16,23 and 4 of 6 pituitary carcinomas 10,13,14,25 that were responsive to temozolomide were the PRL-producing type (Tables 1 and 2), in keeping with the finding by McCormack et al that prolactinomas had a propensity for low-level MGMT expression compared with other tumors. 19 Also noteworthy is the study by Takeshita et al 24 of 7 invasive Crooke cell adenomas, a morphologic variant of corticotrophic adenomas; of these, 5 had low MGMT expression compared with 1 of 17 conventional ACTH-producing adenomas.…”
Section: Mgmt Immunoexpressionsupporting
confidence: 79%
See 2 more Smart Citations
“…19 Of the reported cases, 4 of 11 pituitary adenomas 11,14-16,23 and 4 of 6 pituitary carcinomas 10,13,14,25 that were responsive to temozolomide were the PRL-producing type (Tables 1 and 2), in keeping with the finding by McCormack et al that prolactinomas had a propensity for low-level MGMT expression compared with other tumors. 19 Also noteworthy is the study by Takeshita et al 24 of 7 invasive Crooke cell adenomas, a morphologic variant of corticotrophic adenomas; of these, 5 had low MGMT expression compared with 1 of 17 conventional ACTH-producing adenomas.…”
Section: Mgmt Immunoexpressionsupporting
confidence: 79%
“…49,50 Various combinations, such as cisplatinum, etoposide, and/or paclitaxel, have not achieved sustained responses. 8 Fadul et al 12,13 first reported the successful use of temozolomide in pituitary carcinomas in 2004. Their 2 patients, 1 patient who had systemic metastases of a luteinizing hormone (LH)-producing (gonadotropic) pituitary carcinoma and 1 patient who had a prolactin (PRL)-producing (lactotrophic) carcinoma with spinal dissemination, were treated, and both achieved a sustained response.…”
Section: Pituitary Carcinomasmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown recently that even higher than licensed doses of rosiglitazone (12 mg/day) are not effective in reducing plasma ACTH levels, and by inference tumour growth (45) (figure 1). The orally active alkylating agent temozolomide has been shown to be highly effective in a few aggressive pituitary tumours and in lowering prolactin and controlling tumour growth in highly aggressive prolactinomas (46)(47)(48). Although there are no reports of its use in Nelson's syndrome, temozolomide could be considered in patients with Nelson's syndrome not responding to other modalities of therapy.…”
Section: Medicalmentioning
confidence: 99%
“…In addition, TMZ clinical trials have been performed to test its activity against brain metastatic solid tumors, leukemia (8), pancreatic neuro endocrine tumors (9) and refractory pituitary adenomas (10)(11)(12)(13)(14). Two case studies related to gonadotroph adenoma patients report that their lesions decreased after TMZ therapy (15,16), and studies of TMZ on MMQ, GH3, and AtT20 cell lines suggested that this drug may have efficacy in pituitary adenoma cells (17 to attain biochemical control in a severe case of acromegaly (18). These conflicting data prompted us to further study the effectiveness and mechanism of TMZ on pituitary adenoma cell death in detail.…”
Section: Introductionmentioning
confidence: 99%